Emotional dynamics and regulation in collaborative learning - Törmänen, Tiina; Saqr, Mohammed; López-Pernas, Sonsoles; Mänty, Kristiina; Suoraniemi, Jasmiina; Heikkala, Niklas; Järvenoja, Hanna (Learning and instruction, 2025)
Research has evidenced that students exhibit diverse and fluctuating emotional responses to various stimulus events during collaborative learning, but the empirical evidence on the connections between stimulus events, students’ emotional reactions, and implemented emotion regulation strategies in a collaborative learning context is still scarce. This study aims to explore how group members collaboratively construct emotion regulation in social interaction. Specifically, it investigates students’ emotional reactions in various stimulus events and the related emotion regulation strategies. Ninety-five secondary school students performed a collaborative science task in 31 small groups. The groups' collaboration was videotaped to observe stimulus events, the valence of the students' related emotional reactions, and the emergence of emotion regulation strategies in group members' verbal interactions. Students’ electrodermal activity was recorded to capture their emotional activation. Temporal networks, Markov models, and sequence analysis were used to explore the dynamics between stimulus events, emotional reactions, and emotion regulation strategies. The results showed that the groups’ emotional dynamics centered around three entities: regulating negative emotions caused by task-related and external stimuli by showing empathy and situation modification, supporting each other to manage emotional responses provoked by social stimuli, and enhancing positive emotions in the group using humor and reciprocal positive reactions. This study contributes to the understanding of emotions and emotion regulation in collaborative learning, with implications for educational practice. By employing multimodal multichannel data along with novel learning analytics methods, the study contributes to the advancement of methods used to investigate emotions in learning. •Emotional dynamics in collaborative learning are complex and evolve over time.•Stimulus events most likely triggered negative activating reactions in students.•Situation modification and showing empathy were utilized in task-related events.•Response modulation was used in social-related events.•Humor was used to reinforce a positive emotional state in the group.